2023
DOI: 10.3389/fpsyt.2023.935755
|View full text |Cite
|
Sign up to set email alerts
|

Criminal reactions to drug-using offenders: A systematic review of the effect of treatment and/or punishment on reduction of drug use and/or criminal recidivism

Abstract: The association between substance use and crime is very common, but complex. Several countries have found strategies to face drug abuse and criminality that may exist associated to it, seeking to reduce overcrowded prisons and to promote the reductions of criminal recidivism and/or substance use. Through the guidelines of PRISMA, a systematic review was conducted with the aim to explore the different criminal reactions to individuals who use substances and are involved in the criminal justice system, namely th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 49 publications
1
3
0
1
Order By: Relevance
“…In this review, we observed that most of the interventions aimed at preventing substance abuse were led during imprisonment and that, in at least three of them [18,32,36], participants were followed up after release to determine the effects of the intervention. This is aligned with other authors who state that it is important to adapt the programs to the needs and individual characteristics of each offender in order to achieve a successful intervention [49].…”
Section: Alcohol Drug Abuse and Health Education Interventionssupporting
confidence: 79%
See 1 more Smart Citation
“…In this review, we observed that most of the interventions aimed at preventing substance abuse were led during imprisonment and that, in at least three of them [18,32,36], participants were followed up after release to determine the effects of the intervention. This is aligned with other authors who state that it is important to adapt the programs to the needs and individual characteristics of each offender in order to achieve a successful intervention [49].…”
Section: Alcohol Drug Abuse and Health Education Interventionssupporting
confidence: 79%
“…Apart from alcohol consumption, some of the studies in this review dealt with issues linked to opioids and other substances. The association between substance use and crime is very common but complex [49]. Opioid use disorder is a very common problem in prisons, which can be explained by drug criminalization and, therefore, by people's involvement and use of illegal drugs.…”
Section: Alcohol Drug Abuse and Health Education Interventionsmentioning
confidence: 99%
“…life at a social and economic level (Vergunst et al, 2022). Treatment focused on psychoactive substance abuse can be effective and reduce the risk of drug use and even reoffending (Tomaz et al, 2023). Drug use not only contributes to crime, but also has direct consequences on your mental health and overall well-being.…”
Section: Discussionmentioning
confidence: 99%
“…Der Maßregelvollzug für suchtkranke Rechtsbrecher ist ein deutscher Sonderweg, viele andere Länder kennen dies nicht. Hier werden entsprechende Personen in Gefängnissen betreut [29]. Zur Wirksamkeit der Behandlung suchtkranker Rechtsbrecher im Maßregelvollzug in Bezug auf Suchtmittelkonsum und zukünftige Straffreiheit liegen wenige Studien vor [9,14,[23][24][25].…”
Section: Im Deutschenunclassified